SISTEM INFORMASI PROYEK PESANAN PELANGGAN PADA PT SRI INDAH MANDIRI - Hendry, Hendry; Silalahi, Mesri (LPPM Universitas Putera Batam, 2023)
ABSTRACT In today's rapidly developing technology era, the use of technology is already familiar. Today's human life cannot be separated from the use of technology. PT Sri Indah Mandiri is one of the distributors of building materials on the island of Batam, which provides various kinds of building materials. So far, orders for building materials have been made verbally, namely by telephone or when buyers come directly to the office to place orders. Currently, orders made verbally via telephone often result in miscommunication. When this happens, PT Sri Indah Mandiri as the seller, must resend the goods according to the buyer's order, causing the buyer to be slow in getting the materials he needs, which can disrupt the smooth running of their work. This study aims to design a customer order project information system to improve accuracy and reduce the time to order building materials for PT Sri Indah Mandiri. The system design method used is an agile method with the scrum model. The results of the study show that the designed system can eliminate miscommunication and reduce the time needed to order goods so as to increase the operational efficiency and effectiveness of PT Sri Indah Mandiri.